Work-Family Conflict Affect Employee Performance During The Covid-19 In Jakarta - Gidion Putra Adirinekso; Zenit Zeppelin (Business and Entrepreneurial Review, 2022)
The pandemic has the consequence of increasing workers working from home or WFH. A WFH as a new working style creates problems for workers because they have to concentrate on separating work and family interests. Workers will focus more on work in the office so that distractions from family interests are minor. This study aims to determine the effect of work-family conflict during WFH during the COVID-19 pandemic in Jakarta. The quantitative methods were conducted by distributing questionnaires to married employees who have children, have or are currently experiencing WFH (work from home), and work locations in Jakarta. The technique of processing data using the SEM (Structural Equation Modeling) method using the Smart PLS 3.0 tool. The sample was 114 respondents with a significant level used of 5%. Work-Family conflict is divided into Work Interference, Family and Family Interference Work. The results of this study indicate that the influence of Work Interference Family and Family Interference Work negatively affects employee performance. A statistical test of all hypotheses supports it. WFH is an increasingly developing type of working during a pandemic, which has led to Work-Family conflicts, both in terms of work (WIF) and family (FIW) regarding their performance. From these results, it is interesting to investigate whether the same thing will happen if the type of work is work from the office (WFO).